Assessment of risk perception on microplastics pollution in drinking water sources - Noor Aiza Izzati Mahmod (2021)
Degradation of plastic debris into the size of fewer than 5 millimeters in the marine environment has become a global issue. Plastics debris such as polystyrene, plastic straw, and plastics bags are significant contributors to this microplastics issue. The microplastics particles can accumulate in the freshwater system, becoming the source of drinking water. Microplastics particles in drinking water sources will pose a threat to human health and the environment. However, they are a lot of people who are not aware of these risky situations. Therefore, a survey has been conducted on Universiti Malaysia Kelantan students from all campuses towards the risk perception of microplastics pollution in drinking water sources to increase awareness regarding this microplastic pollution. On top of that, this study aims to measure the level of risk perception and the relationship between risk perception, concern and behavioural intentions of the respondents towards microplastics pollution in drinking water sources. In this study, questionnaires are distributed on an online platform to conduct the survey. About 320 respondents from Universiti Malaysia Kelantan were involved in this survey. Analysis of independent t-test, ANOVA, correlation and multiple linear regression has been used to analyse the data. Approximately 93.13% of respondents agreed with the risk perception section statement, where they were aware of microplastics' presence in their surroundings. There were 96.25% of the respondents concerned about microplastics pollution and 94.06% of respondents have high behavioural intentions to reduce microplastic pollution in drinking water sources. The results show a positive correlation between each variable. However, multiple linear regression analysis shows that the behavioural intentions do not significantly affect the level of respondents’ risk perceptions.